Guidance from the Scientific and Standardization Committee for lupus anticoagulant/antiphospholipid antibodies of the International Society on Thrombosis and Haemostasis: Update of the guidelines for lupus anticoagulant detection and interpretation - Devreese, Katrien M J; de Groot, Philip G; de Laat, Bas; Erkan, Doruk; Favaloro, Emmanuel J; Mackie, Ian; Martinuzzo, Marta; Ortel, Thomas L; Pengo, Vittorio; Rand, Jacob H; Tripodi, Armando; Wahl, Denis; et al. (Journal of thrombosis and haemostasis, 2020)
This guidance focuses on methodological aspects of lupus anticoagulant (LA) testing, as well as interpretation of results for clinicians. The main changes in how to test for LA compared with the International Society on Thrombosis and Haemostasis Scientific and Standardization Committee 2009 guidelines, in the preanalytical phase are more detailed recommendations on how to handle testing in anticoagulated patients, and the timing of testing. Also, routine coagulation tests are advised to obtain more information on the coagulation background of the patient, and when necessary, anti-Xa activity measurement for heparins or specific assays for direct oral anticoagulants should be performed. The three-step procedure with two test systems (diluted Russell's viper venom time and activated partial thromboplastin time [aPTT]) is essentially not changed. Silica remains the preferable activator in the aPTT assays, but ellagic acid is not excluded. We advise simultaneous performance of the mixing and confirmatory step, in each sample with a prolonged screening test. The confirmatory step can also be performed on a mixture of patient plasma and normal pooled plasma. Cutoff values should be established in-house on at least 120 normals, with transference of the manufacturer's cutoffs as an alternative. Reporting of results has not been changed, although more attention is focused on what clinicians should know. Patient selection for LA testing has been expanded.